Dinamika Pendidikan Agama Kristen pada Masa Pandemi Covid-19: Analisis Kompetensi Pedagogik Yesus dalam Injil Matius - Victorius Wau (Sekolah Tinggi Teologi Berita Hidup, 2020)
The period of the Covid-19 pandemic is a period of transition for the world, including in the field of education, which is the right of everyone. During the transition period, the government has decided to carry out the online teaching and learning process by using conference calls or social media. This model is now used by almost all educational institutions in Indonesia. In this case, of course, there are striking differences in the teaching and learning process, including with Christian Education. Therefore, the distance learning process of Christian Education can emulate the pedagogical competence of Jesus in Matthew's Gospel to be applied during this pandemic, so that the three educational domains (cognitive, affective and psychomotor) can be achieved properly. The method in writing this paper is descriptive qualitative, observing the book of Matthew and observing the dynamics of education during the pandemic via the internet and direct actions experienced by schools in Indonesia. The conclusion of this paper is that the teacher must imitate Jesus' pedagogy, such as: the teacher must know the character of the student, the teacher must be communicative with structured and creative material, the teacher can use the discovery learning method, the teacher must provide teaching based on the child's needs, and the teacher must continue to teach basic things in a child's life.Masa pandemi Covid-19 adalah masa transisi bagi dunia, termasuk di bidang pendidikan yang adalah hak setiap orang. Di masa transisi, pemerintah telah menetapkan untuk melakukan proses kegiatan belajar mengajar (KBM) secara daring dengan menggunakan conference call atau media sosial. Model ini kini digunakan hampir seluruh lembaga pendidikan di Indonesia. Dalam hal ini tentu ada perbedaan yang mencolok dalam proses KBM, tidak terkecuali dengan Pendidikan Agama Kristen (PAK). Maka dari itu, dalam proses pembelajaran PAK jarak jauh dapat meneladani kompetensi pedagogik Yesus dalam Injil Matius untuk diterapkan di masa pandemi ini, sehingga tiga ranah pendidikan (kognitif, afektif dan psikomotorik) tetap tercapai dengan baik. Metode dalam penulisan karya tulis ini adalah deskriptif kualitatif, mengamati kitab Matius dan pengamatan dinamika pendidikan di masa pandemi lewat internet dan tindakan langsung yang dialami oleh sekolah-sekolah di Indonesia. Kesimpulan dari karya tulis ini adalah guru harus meneladani pedagogik Yesus, seperti: guru harus mengenal karakter murid, guru harus komunikatif dengan materi yang terstruktur dan kreatif, guru dapat menggunakan metode discovery learning, guru harus memberikan pengajaran berdasarkan kebutuhan anak, dan guru harus tetap mengajarkan hal-hal yang mendasar dalam kehidupan anak.